The attitudes of employees towards the relationship of organizational variables to the effectiveness of the job performance - Al-Salami, Yamama (Journal of Economic, Administrative and Legal Sciences, 2017)
Organizations are working hard for improving their employee performance to meet their intended strategic goals. This entails to activate the role of the organizational changes in the work’s internal environment. This paper highlights the most important organizational changes that improve the effectiveness of employee performance. Furthermore, the paper identifies the employees’ attitudes in Babylon Investment Commission of Iraq regarding the relationship between organizational changes and the employees’ performance. Results reveal that the organizational changes have a positive impact on employees’ performance which is obviously reflects the organizational performance. Further, results showed no difference between the answers of respondents on what concern the relationship between organizational changes and the employee performance. The questionnaire includes questions about gender, age, official performance, academic qualification, official experience and administrative level.
Keywords: job performance; organizational variables; Babel Investment Authority